Panggilan Katekis di Tengah Revolusi Industri 5.0: Menyikapi Pesan Paus Fransiskus dalam Dokumen Antiquum Ministerium - Julianti Fingki; Fabianus Selatang (STIKAS Santo Yohanes Salib Kalimantan Barat, 2025)
The Industrial Revolution 5.0 has a significant impact on social, economic, and cultural life, including religious practices. At the same time, the Antiquum Ministerium document issued by Pope Francis emphasizes the importance of the role of catechists in guiding the faithful towards a deeper understanding of the faith. Therefore, there needs to be an adjustment of catechesis methods and approaches in order to be able to answer the challenges and needs of today's generation who are familiar with technology. The purpose of this paper is to analyze how catechists can carry out and adapt their life callings in the context of the Industrial Revolution 5.0, as well as to identify the challenges they face in facing the changing times and develop effective strategies for Catholic faith education in the digital age. The method used in this study is a literature study. Literature study is a series of activities related to the method of collecting library data, reading and recording and processing research materials. Literature studies study various reference books as well as the results of previous research. Catechists have an important role to play in teaching and fostering the faith of the people, serving as an example that reflects the teachings of Christ, especially in the context of the Industrial Revolution 5.0 which emphasizes social welfare and the use of technology. In the midst of rapid change, they are expected to bridge the gap between faith and technology, leveraging digital advancements to achieve the catechesis mission. Thus, catechists not only contribute to the teaching of doctrine, but also become agents of change who spread the values of love and hope to society.